LINGUOCULTURAL ASPECT OF RESEARCH TOPONYMS - Khakimova Khurshida Bakhtiyarovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
The article examines the problem of the linguocultural aspect of the study of toponyms. Particular attention is paid to work carried out in line with the cognitive and functional approaches to the analysis of toponymic material. The main directions of research of toponyms within the framework of these approaches are described.